2000
DOI: 10.1016/s0895-7061(00)01185-7
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and antihypertrophic effects of omapatrilat in SHR

Abstract: Vasopeptidase inhibitors, such as omapatrilat are single molecules that simultaneously inhibit neutral endopeptidase (NEP) and angiotensin converting enzyme (ACE). In normotensive rats, a single dose of oral omapatrilat (10 mg/kg) and 1 mg/kg inhibited plasma ACE (P < .01) for 24 h and increased plasma renin activity for 8 h (P < .01). In vitro autoradiography using the specific NEP inhibitor radioligand 125I-RB104 and the specific ACE inhibitor radioligand 125I-MK351A showed omapatrilat (10 mg/kg) caused rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
4
26
2
Order By: Relevance
“…NEP inhibition: For NEP in vitro autoradiography, the p-nitrophenolic ester of RB104, a specific NEP inhibitor ligand (0.51 µg in 5.1 µl) was iodinated according to a minor modification of a previously published method using 1 mCi of 125 I (Amersham Radiochemicals, Amersham, UK) and chloramine T (25 µg in 50 µl) [29]. Autoradiography was done as previously described [15,19]. Quantification of binding density was determined by computerised densitometry and the optical density of the autoradiographs was converted to dpm·mm −2 with the use of radioactive standards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NEP inhibition: For NEP in vitro autoradiography, the p-nitrophenolic ester of RB104, a specific NEP inhibitor ligand (0.51 µg in 5.1 µl) was iodinated according to a minor modification of a previously published method using 1 mCi of 125 I (Amersham Radiochemicals, Amersham, UK) and chloramine T (25 µg in 50 µl) [29]. Autoradiography was done as previously described [15,19]. Quantification of binding density was determined by computerised densitometry and the optical density of the autoradiographs was converted to dpm·mm −2 with the use of radioactive standards.…”
Section: Methodsmentioning
confidence: 99%
“…VPIs simultaneously inhibit ACE and NEP, thereby acting to decrease circulating levels of vasoconstrictor effector molecules such as angiotensin II (AII) as well as increasing the levels of vasodilatory agents such as atrial natriuretic peptide and bradykinin (BK) [12,13]. Previous research using the first of the VPIs, omapatrilat, has examined the beneficial effects on ameliorating developing clinical and experimental hypertension [14,15,16]. In addition, an increasing number of studies have explored these agents in models of non-diabetic renal disease [13,17,18].…”
mentioning
confidence: 99%
“…In various experimental models of hypertension, heart disease and renal disease combined ACE/NEP inhibition led to more potent and synergistic hemodynamic and renal effects than selective inhibitors of the individual enzymes. The antihypertensive 7 and antifibrotic effects [8][9][10] were associated with enhanced vasodilation, natriuresis and improved myocardial function.…”
Section: Neutral Endopeptidase Inhibitionmentioning
confidence: 99%
“…Omapatrilat appears to dissociate from tubular NEP active sites more rapidly than from tubular ACE active sites, which is in accordance with data obtained in rats. Burell et al (23) have shown that although the Ki for both ACE and NEP is very similar in vitro (NEP, 8.9 nM; ACE, 6 nM), 24 h after the administration of a single oral dose of 10 mg/kg omapatrilat to normotensive rats, renal ACE was inhibited by more than 75%, whereas renal NEP was only inhibited by 30%. This profile is probably characteristic of omapatrilat.…”
Section: Effects Of Omapatrilat On Ace and Nep Inhibitionmentioning
confidence: 99%